Length of Critical Patient Care is Related to Family Anxiety Level in the Intensive Care Unit of PKU Muhammadiyah Bantul Hospital - Poku, Siti Rahmawati B.; Azizah, Aisyah Nur (Poltekkes Kemenkes Aceh, 2024)
Background: Intensive Care Unit (ICU) is a hospital intensive care unit for patients who experience impaired vital organ function with critical conditions and require continuous care, treatment and monitoring. This makes the patient's family unable to fully accompany the patient while being treated in the ICU. This often causes family anxiety regarding the news and condition of the patient during treatment, so this psychological problem can reduce the family's quality of life if it continues for a long time. Purpose: To find out the relationship between the length of critical patient care and the level of family anxiety in the ICU. Methods: Quantitative research type with cross sectional survey design. The sampling technique used total sampling with a total sample of 40 people. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) instrument. Data analysis was carried out using the Spearman correlation test. Results: The results of the Spearman rank test obtained a significant value of 0.001 <0.05 indicating that there is a significant relationship between the variable of the length of critical patient care and the level of family anxiety. The correlation coefficient value obtained a value of 0.517 which means that the relationship between the two variables is strong with a positive correlation number. Conclusion: There is a significant relationship between the length of critical patient care and the level of family anxiety in the ICU. The longer the hospitalization of critical patients, the higher the level of family anxiety.